2022
DOI: 10.1111/scd.12809
|View full text |Cite
|
Sign up to set email alerts
|

Prosthodontic restoration of a COVID‐19 associated mucormycosis defect: A clinical report

Abstract: Introduction Coronavirus Disease 2019 (COVID‐19) pandemic brought the clinical practice of dentistry and prosthodontics at the threshold of a new era, due to the increasing prevalence of a relative rare condition normally affecting the immunocompromised patients. Aim The aim of this clinical case report is to briefly describe the etiopathogenesis, the surgical and prosthodontic management of this evolving medical condition emphasizing the emerging role of the maxillofac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…27 Recent case reports have documented 10 patients with history of post covid mucormycosis (PCM) who were efficiently rehabilitated with obturators (Table 1, Table 2). [19][20][21][22][23]28,29 Diabetes mellitus was the most significant associated risk factor in 27 patients followed by Acute Myeloid Leukemia based on data reported here and earlier by Santos et al Rhizopus oryzae has been reported to be the most common causative organism as high glucose levels, insulin resistance and ketoacidosis encourage its growth. 30 Amphotericin B remained the first-choice drug followed by Posaconazole.…”
Section: Data Acquisition and Observationsmentioning
confidence: 78%
See 2 more Smart Citations
“…27 Recent case reports have documented 10 patients with history of post covid mucormycosis (PCM) who were efficiently rehabilitated with obturators (Table 1, Table 2). [19][20][21][22][23]28,29 Diabetes mellitus was the most significant associated risk factor in 27 patients followed by Acute Myeloid Leukemia based on data reported here and earlier by Santos et al Rhizopus oryzae has been reported to be the most common causative organism as high glucose levels, insulin resistance and ketoacidosis encourage its growth. 30 Amphotericin B remained the first-choice drug followed by Posaconazole.…”
Section: Data Acquisition and Observationsmentioning
confidence: 78%
“…5 I. E. Ali, et al reported prosthodontic rehabilitation of post mucormycosis defects from 30 case reports published between 2010 to 2021. 24 18 more patients on PubMed [17][18][19][20][21][22][23] and 9 on google scholar [Table 2] were reported with history of mucormycosis followed by fabrication of palatal obturator from 2020 to May 2023. Mean age and gender wise distribution of patients who were rehabilitated after surgical management of mucormycosis has been depicted in Figure 1.…”
Section: Data Acquisition and Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the cases of post- COVID-19-associated ROM defect reported in the literature have been rehabilitated prosthetically using intraoral obturators, partial dentures, palatal flaps, and other soft-tissue flaps. 5 17 A recent study by Gupta et al 18 used ALT flaps for covering COVID-19-associated mucormycosis defects in 14 patients. All flaps in their study survived, without any major or minor complications.…”
Section: Discussionmentioning
confidence: 99%